Bacterial cellulose–poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) composites for optoelectronic applications. (20th August 2015) - Khan, Shaukat; Ul-Islam, Mazhar; Khattak, Waleed Ahmad; Ullah, Muhammad Wajid; Park, Joong Kon
Highlights: BC–PEDOT:PSS composites were synthesized by ex situ penetration method. XPS, XRD, FTIR, and SEM analysis confirmed the successful synthesis of composites. The composites showed high conductivity. These composites can find potential applications in optoelectronic devices. Abstract: Electrically conducting bacterial cellulose (BC) membranes were prepared by ex situ incorporation of poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS) into BC pellicles. The BC pellicles were immersed into an aqueous solution of PEDOT:PSS for 6, 12, 18, or 24 h, and the resultant composites were vacuum dried at ambient temperature. The structural features of the composites were determined using X-ray photoelectron spectroscopy (XPS), field-emission scanning electron microscopy (FE-SEM), Fourier-transform infrared (FTIR) spectroscopy, and X-ray diffraction (XRD). XPS confirmed synthesis of the composites, and SEM showed uniform incorporation of PEDOT:PSS into the BC matrix. The FTIR spectra of the composites exhibited characteristic bands for both BC and PEDOT:PSS, and XRD analysis showed a slight decrease in crystallinity during composite preparation. The electrical conductivity of the composites was 12.17 S/cm for incorporation of 31.24 wt% PEDOT:PSS into the BC matrix. These highly conducting BC–PEDOT:PSS composites are expected to find potential applications in optoelectronic devices such as biosensors, organic light-emitting diodes, and solar cells.